2018
DOI: 10.1002/bmc.4387
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a hydrophilic interaction ultra‐high‐performance liquid chromatography–tandem mass spectrometry method for rapid simultaneous determination of 19 free amino acids in rat plasma and urine

Abstract: Determination of amino acids in biofluids is a challenging task because of difficulties deriving from their high polarity and matrix interference. A simple, reliable and highthroughput hydrophilic interaction UHPLC-MS/MS method was developed and validated for the rapid simultaneous determination of 19 free amino acids in rat plasma and urine samples in this paper. Hydrophilic method with a Waters Acquity UPLC BEH Amide column (100 × 2.1 mm,1.7 μm) was used with a gradient mobile phase system of acetonitrile an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…LC–MS conditions for targeted metabolomics analysis: Targeted metabolomics analysis was carried out as previously described by Wen et al (2019) with modifications. Samples were kept at 8°C in the autosampler and 0.5 μl were randomly injected to an ACQUITY I CLASS UPLC system (Waters), equipped with an ACQUITY UPLC BEH amide column (2.1 mm × 100 mm, 1.7 μm; Waters) and a guard column BEH amide Vanguard Pre‐column (2.1 mm × 5 mm, 1.7 μm; Waters) maintained at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…LC–MS conditions for targeted metabolomics analysis: Targeted metabolomics analysis was carried out as previously described by Wen et al (2019) with modifications. Samples were kept at 8°C in the autosampler and 0.5 μl were randomly injected to an ACQUITY I CLASS UPLC system (Waters), equipped with an ACQUITY UPLC BEH amide column (2.1 mm × 100 mm, 1.7 μm; Waters) and a guard column BEH amide Vanguard Pre‐column (2.1 mm × 5 mm, 1.7 μm; Waters) maintained at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome these drawbacks, HILIC, an alternative method for the separation of polar compounds such as amino acids, was used. High polar compounds not only would have better retention and separation in the HILIC method but also do not require the traditional derivatization steps or ion-pairing separations [21]. e liquid chromatography was optimized on an HILIC column.…”
Section: Lc-ms/ms Methods Development Several C18 and C8mentioning
confidence: 99%
“…HILIC could overcome the drawback of poor solubility, poor analytical reproducibility, and limited compatibility with electrospray ionization mass spectrometry that are often encountered in normal-phase HPLC. It was observed that analytes can be eluted similarly to normal phase liquid chromatography in the mobile phase of a reversed-phase system [19,20,21]. erefore, HILIC may hold promise as an alternative method for quantitative analysis of ASN concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Both solvent A (water with 0.2% CH 2 O 2 ) and solvent B (CH 3 CN with 0.2% formic acid) flowed at a rate of 0.3 mL/min down the column as the stationary phase. The AAs detected in plasma were alanine, Val, proline, Trp, phenylalanine, methionine, glycine, serine, Cys, Tyr, asparagine, glutamine, lysine, arginine, His, aspartic acid, glutamic acid, and trans ‐4‐hydroxyproline, and AAs detected in urine were alanine, Val, proline, phenylalanine, Trp, methionine, glycine, serine, threonine, Cys, Try, asparagine, glutamine, lysine, arginine, His, aspartic acid, glutamic acid, and trans ‐4‐hydroxyproline, and their RT was in the range of 2.89–6.61 min [27].…”
Section: Bioanalytical Approachesmentioning
confidence: 99%